Executive functions and associated brain volumetry in children with persistent stunting and catch-up growth - Beena Koshy; Vedha Viyas Thilagarajan; Roshan S. Livingstone; Manikandan Srinivasan; Venkata Raghava Mohan; Rachel Beulah; Anitha Jasper; Sushil John; Gagandeep Kang (Scientific Reports)
Abstract Early childhood stunting can result in sub-optimal executive functions (EF), affecting academic achievements and economic potential in later life. This study hypothesized that children always stunted (AS) at ages 2, 5 and 9 years had lower EF than those who were never stunted (NS). A birth-cohort in Vellore, India was followed up with periodic anthropometric and development/cognitive measures over 2, 5 and 9 years of age. Based on stunting status at these time points, children were classified as NS, stunted at 2 years and caught up by 5 years (S2N5), stunted at 2 and 5 years but caught up later (S5N9), and AS. At 9th year, children underwent neuroimaging using 3T MRI scanner and EF assessment using FAS phonemic fluency test, colour cancellation test and colour trials tests (CTT). From the original birth-cohort of 251, 205 children were reviewed at 9 years. FAS phonemic fluency test showed NS group had significantly higher test scores compared to AS (11.52 vs. 7.4, p = 0.02). In CTT, a significant difference in near misses score was observed between NS and AS groups (0.12 vs. 0.38, p = 0.03). Upon evaluating unimodal brain association areas, volumes of right occipital fusiform gyrus (9991 mm3 vs. 9313 mm3; p = 0.04; η2 = 0.11), and left lateral occipital cortex (13458 mm3 vs. 12559 mm3; p = 0.03; η2 = 0.07) were significantly higher among NS compared to AS group. Considering higher order association areas, only left pars triangularis was found to be significantly reduced among AS children compared to NS group (4284 mm3 vs. 3291 mm3; p = 0.01; η2 = 0.07). Similarly, there were also significance visible in the basal ganglia regions and the cerebellum. Current study demonstrated EF dysfunction in verbal fluency and inhibitory control in a dose response fashion in groups AS-to-NS with corresponding EF-related brain volumetric changes, highlighting the need for focused nutritional and nurturing approaches in early childhood for gain in human capital.